Silicon and heavy metal dynamics in soil-rice systems: A taihu lake plain case study on silicon depletion - Yumeng Lu; Sihua Huang; Gaili He; Ye Yuan; Jiahao Zhai; Xiaoqing Wang; Dejing Chen; Lijie Pu (Ecotoxicology and Environmental Safety)
This study addresses the critical issue of heavy metal contamination (Ni, Cu, As, Cd, Pb) in rice cultivation, with particular focus on silicon-deficient paddy soils in the Taihu Lake Plain, where SiNaAc is 87.97 mg kg−1. While silicon (Si) supplementation has demonstrated efficacy in mitigating heavy metal stress in plants, its effectiveness in Si-deficient soil-rice systems remains insufficiently characterized, particularly at the field scale. Our investigation of four typical crop rotation systems revealed significant contamination risks from As and Cd, with plant-available silicon (PaSi) predominantly influencing the active fractions of these metals. Key factors governing heavy metal accumulation in brown rice included soil metal content (HMsSoil), soil PaSi (PaSiSoil), and plant Si (SiPlant), exhibiting strong predictive power for As (R²=0.69), Cd (R²=0.51), and Cu (R²=0.59) accumulation. Structural equation modeling identified dual mechanisms of Si-mediated metal regulation: direct modulation in the Husk-Brown Rice transfer pathway and indirect suppression through Root-Straw translocation. These findings elucidate Si's pivotal role in impeding heavy metal transfer from soil to edible grains, highlighting the potential of strategic Si fertilization as an effective agronomic intervention for minimizing dietary heavy metal exposure and enhancing food safety in contaminated rice production systems.